PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING TERHADAP MOTIVASI BELAJAR SISWA - Suryani, Rina; Wahyudi, Chandra; Sinaga, Daniel Osvaldo; Nasution, M. Ikhwanul Arfan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research aims to determine the effect of role playing technique group guidance service on students learning motivation. The formulation of the problem in this research is: Is there an influence of role playing technique group guidance service on the students learning motivation? The research method used in this research is a quantitative method. The subjects of this research were 10 students in class X students of SMA Negeri 10 Medan for the 2022/2023 academic year who had low learning motivation scores. The instrument used is a student learning motivation scale consisting of 35 valid and reliable question items. Instruments were given before and after the implementation of group guidance services. The data analysis technique used in this research is the Wilcoxon analysis technique with α = 0.05. The results of this research show that before (pre-test) the role playing technique group guidance service was carried out it was 65.3. After (post-test) the role playing technique group guidance service was carried out it was 95.8. The Wilcoxon test results with the smallest rank value, namely 25. So J_count = 25, α = 0.05, n=10, then we get J_table = 8. Based on the results of the Wilcoxon test, J_count > J_tabel is obtained where 25 > 8. So it can be said that there is an “effect of role playing technique group guidance service on learning motivation”. Hypothesis can be accepted.